Science and Technology for the Community Compilation of Financial Statements Based on SAK ETAP - Subhan Subhan (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
The PkM program developed is the implementation of preparing financial reports based on Entity Financial Standards Without Public Accountability (SAK ETAP). SAK ETAP is a standard issued by the Indonesian Accounting Standards Board (DSAK) that must be applied by all companies. The method used in implementing this PkM activity program is the provision of counseling and training to partner employees using direct methods for transactions that occur in company activities. The results of the activity are expected that partner employees can know and carry out the preparation of financial reports based on Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP).